Preferential adsorption to air–water interfaces: a novel cryoprotective mechanism for LEA proteins. Issue 7 (10th April 2019) - Yuen, Fanny; Watson, Matthew; Barker, Robert; Grillo, Isabelle; Heenan, Richard K.; Tunnacliffe, Alan; Routh, Alexander F.
Abstract : Late embryogenesis abundant (LEA) proteins comprise a diverse family whose members play a key role in abiotic stress tolerance. As intrinsically disordered proteins, LEA proteins are highly hydrophilic and inherently stress tolerant. They have been shown to stabilise multiple client proteins under a variety of stresses, but current hypotheses do not fully explain how such broad range stabilisation is achieved. Here, using neutron reflection and surface tension experiments, we examine in detail the mechanism by which model LEA proteins, AavLEA1 and ERD10, protect the enzyme citrate synthase (CS) from aggregation during freeze–thaw. We find that a major contributing factor to CS aggregation is the formation of air bubbles during the freeze–thaw process. This greatly increases the air–water interfacial area, which is known to be detrimental to folded protein stability. Both model LEA proteins preferentially adsorb to this interface and compete with CS, thereby reducing surface-induced aggregation. This novel surface activity provides a general mechanism by which diverse members of the LEA protein family might function to provide aggregation protection that is not specific to the client protein.